Digital Transformation of Victim Reporting Systems: Applying DEG Framework to Indonesia’s SIMFONI PPA - Novalia Novalia; Nandang Alamsah Deliarnoor; Antik Bintari (Journal of Social Work and Science Education, 2026)
The digitalization of public services in the women and child protection sector faces challenges including institutional fragmentation, weak data integration, and limited regional capacity. This study analyzes the application of Digital Era Governance (DEG) in the Online Information System for Women and Child Protection (SIMFONI PPA), Indonesia’s national system for recording and reporting violence victims. Using a qualitative case study design, data were collected through in-depth interviews (n = 15 key informants including ministry officials, regional UPTD heads, and service users), observations, and analysis of regulations, policy documents, and digital sources (2024-2026). Thematic coding based on DEG’s three dimensions reintegration, needs-based holism, and digitalization revealed three main findings. First, SIMFONI PPA functions as a governance reintegration tool by unifying workflows and data across central and regional governments without formal institutional restructuring. Second, the system promotes a holistic, needs-based service orientation by facilitating continuous case handling and victim-centered data integration. Third, digitalization has not fully resulted in equitable governance transformation due to persistent disparities in human resource capacity, infrastructure, and cross-sector integration at local levels. The study contributes to digital governance literature by extending DEG framework application to gender-based violence recording systems. Limitations include single-country focus and limited cross-sectoral data integration analysis. Policy implications emphasize strengthening local capacity, expanding interoperability with health and legal systems, and balancing digital standardization with contextual service practices.